A framework for capturing structural variation in flipped mathematics instruction. Issue 5 (28th May 2023) - Otten, Samuel; de Araujo, Zandra; Sherman, Milan; Birişçi, Salih
ABSTRACT: Teachers are implementing flipped instruction in an increasing number of mathematics classes but the research base is not yet well developed on this topic. Many studies of flipped instruction in mathematics have involved a small number of classes utilizing flipped instruction being compared to classes with non-flipped instruction, but this study design fails to account for variations in how teachers implement flipped instruction. There seems to be as much variation within flipped implementations and within non-flipped implementations as there are between the two categories. To aid systematic attention to variation, this article presents a framework for flipped mathematics lessons that identifies key features of the videos assigned as homework as well as features of the in-class time with students. The components of the framework allow for structurally similar implementations to be grouped together meaningfully whereas different implementations, though still under the banner of 'flipped instruction', can be distinguished from one another. The framework is illustrated with data from flipped mathematics classes at secondary and post-secondary levels.